MEMBANGUN KREATIVITAS DAN KEMANDIRIAN MASYARAKAT KELURAHAN LOSUNGBATU KOTA PADANGSIDIMPUAN PADA MASA PANDEMI COVID-19 - Silviana Batubara; Fithra Maharani; Makhrani Makhrani (LP2M STP Mataram, 2021)
The outbreak of the Covid-19 virus in Indonesia causes disturbances in the respiratory system, severe lung infections that can cause death. Not only caused a high death rate worldwide, the outbreak of this virus resulted in a contraction of economic growth, slow economic decline and killed countries around the world and also resulted in a large number of unemployed. Another impact of the outbreak of the Covid-19 Virus is the occurrence of morbidity where many residents are unable to work for a certain period of time. This Community Service aims to help the people of Losungbatu Village, Jalan Rukun No.28, Padangsidimpuan in building creativity and independence of the community in the economic field during this Covid-19 period